Transmission Electron Microscope Study of Melanocytes on the Mongolian Blue Spot Region - Tsedendorj, Batchimeg; Amgalanbaatar, Avirmed; Bold, Juramt; Dorjkhuu, Amgalanbaatar; Dalkhsuren, Shine-Od (Central Asian Journal of Medical Sciences, 2020)
Objectives: We aimed to study the melanocyte and melanin granules of the blue spot skin. Methods: The skin specimens were taken from the sacral region of a 1 and an 8 month old child and a 35 year old man. We proceeded to examine the melanocytes of the blue spot and non-blue spot regions by light and transmission electron microscope analysis. Results: TThe melanocytes of the sacral skin of the adult man were found on the epidermal side of the epidermal-dermal junction. The cytoplasm of the melanocyte contained melanin granules of the dense type. The melanocytes of the blue spot skin of the 1 and 8 months old children were found at the uniformly thin basal membrane of the epidermis. The cytoplasm of these melanocytes contained melanin granules of both light and dense types. There were distinct differences in the thickness of the basal membrane, and in the size and composition of the melanin granules. Conclusion: Melanocytes of the sacral blue spot region were located on the basal membrane of the epidermis near to the epidermal-dermal junction. The cytoplasm of the melanocytes contained melanin granules of both dense and light types.